Approximation by Half Terms of Baskakov-Kantorovich Sequence of Linear Positive Operators - Jaddoa, Ali A.; Mohammad, Ali J. (Communications in Mathematics and Applications, 2024)
This paper modified the Baskakov-Kantorovich sequence by taking the half terms of the sequence. Firstly, the convergence of this sequence was shown using Korovkin’s theorem. Secondly, the Voronovskaja-type asymptotic theorem for this sequence is established. Finally, this sequence gives two numerical examples to approximate two test functions. Then, the numerical outcomes will be contrasted with those of the corresponding classical sequence. Compared to the classical sequence, the modified sequence produces superior numerical results.